Middle of the night - Sager, Riley (New York : Dutton, an imprint of Penguin Random House LLC, 2024)
"A man must contend with the long-ago disappearance of his childhood best friend-and the dark secrets lurking just beyond the safe confines of his picture-perfect neighborhood."--
Keywords: Missing persons -- Fiction; Best friends -- Fiction; Cold cases (Criminal investigation) -- Fiction; Ghosts -- Fiction; New Jersey -- Fiction; Psychological fiction; Horror fiction; Thrillers (Fiction)